The Role of Micro Waqf Banks in Increasing Income Community in Banjaririgasi Village - Hamzah, Hannisha; Vianka, ‎; Azzahra, Syaharani; Priyono, Budi (KnE Social Sciences, 2025)
Lebakgedong is a district in Banten Province, Lebak Regency and has an underdeveloped status with the smallest Gross Regional Domestic Product (GRDP) per capita at current prices in this province from 2021 with a figure of 22,011, then there was an increase in 2022 with a figure of 23,617, and finally in 2023 with a figure of 24,816.66. The average value of the Village Development Index (VDI) obtained by Lebakgedong District was 0.54192 in 2023 (Directorate General of Village and Rural Development, 2023). Thus, it is necessary to increase community income as an effort to improve the quality of lives of village communities, and one way of doing that is through the Micro Waqf Bank. Micro Waqf Bank Lan Taburo is a cooperative of Islamic Microfinance Institutions (IMI) which has financed 68 kumpi consisting of 1700 cumulative customers with a cumulative financing amount of 3.7 billion, and financed 215 outstanding customers with a financing amount of 176.7 million. However, there is still a lack of understanding and awareness of the potential and benefits of Micro Waqf Bank among the community and MSME actors in Lebakgedong District. So, this study aims to find out how BWM Lan Taburo can increase community income in Banjaririgasi Village. This study uses a qualitative research method by looking at literature studies and conducting field reviews. Data collection methods use interview techniques, observation, and literature studies. The results of the study show that BWM Lan Taburo is able to empower the community through socialization and training programs for business actors and provide capital financing to business actors so that they can simultaneously increase community income.